Origins of the fastest master breaststroke swimmers - Knechtle, Beat; Santos Andrade, Marilia; Ahmad, Wais; Forte, Pedro; Moreitz, Sascha; Stanula, Arkadiusz; Nikolaidis, Pantelis Theo; Cuk, Ivan; Thuany, Mabliny; Weiss, Katja; Rosemann, Thomas; Seffrin, Aldo (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Purpose. Specific performance-related aspects of the breaststroke have been thoroughly investigated in sports science. How-ever, the nationalities of the fastest master breaststroke swimmers are unknown. The present study investigated the nationalities of the fastest master breaststroke swimmers.Methods. For all World Masters Championships held between 1986 and 2024, the year of competition, first name, last name, age, age group, stroke, and distance were recorded for each swimmer. Descriptive data were presented using mean, standard deviation, maximum, minimum, and/or confidence intervals. The top 10 race times for each sex were identified, with the nation-alities sorted into six categories. The data were then grouped into the top five nationalities with the most appearances in the breaststroke swimming top 10 by distance each year and all other nationalities. The Kruskal–Wallis H test compared nationality differences, followed by Bonferroni-adjusted pairwise comparisons to identify specific distinctions.Results. Between 1986 and 2024, most swimmers (40.7%) competed in the 50 m event (n = 17575; 7911 women and 9664 men), followed by the 100 m (35.2%, n = 15211; 7158 women and 8053 men), and the 200 m events (24.0%, n = 10373; 4934 women and 5439 men). Germany had the most women swimmers in the top 10 yearly, whereas the country with the highest number of men swimmers in the top 10 per year was the United States of America (USA). Germany, Great Britain, the USA, and Italy were the most frequent nationalities among the top 10 countries across all women’s breaststroke distances. For men, the USA, Russia, Germany, and Italy were among the top 10 countries in all men’s breaststroke distances. In general, performance differences were observed among various countries across all breaststroke distances for both men and women, with certain countries consistently outperforming others in specific events. Germany tended to have better performances for women, while Russia excelled in the men’s events.Conclusions. In summary, differences exist in swimming distance and athlete origin of the fastest master breaststroke swim-mers. Germany, Great Britain, the USA, and Italy were the most frequent nationalities among the top 10 countries annually in all women’s breaststroke distances. For men, the USA, Russia, Germany, and Italy were among the top 10 countries in all men’s breaststroke distances.
Keywords: endurance; water sport; performance; discipline; nationality